Time Series Analysis of Export Demand Equations : A Cross-Country Analysis - Montenegro, Claudio (IMF Working Papers; Working Paper ;, 1998)
The paper estimates export demand elasticities for a large number of developing and developed countries, using time-series techniques that account for the nonstationarity in the data. The average long-run price and income elasticities are found to be approximately -1 and 1.5, respectively. Thus, exports do react to both the trade partners' income and to relative prices. Africa faces the lowest income elasticities for its exports, while Asia has both the highest income and price elasticities. The price and income elasticity estimates have good statistical properties.